Upaya Peningkatan Produksi Kelapa Sawit melalui Penerapan Teknik Konservasi Tanah dan Air - Murtilaksono, Kukuh; Darmosarkoro, Witjaksana; Sutarta, Edy Sigit; Siregar, Hasril Hasan; Hidayat, Yayat (UNIVERSITY OF LAMPUNG, 2009)
Effort to Increase Oil Palm Production through Application Technique of Soil and Water Conservation (K. Murtilaksono, W. Darmosarkoro, E.S. Sutarta, H. H. Siregar, and Y. Hidayat): The study was carried out at block 375, 415, and 414 (block 1, 2, and 3) Afdeling III, Mangement Unit of Rejosari, PT Perkebunan Nusantara VII, Lampung from June 2005 until December 2007. Objective of the study is to examine the effect of soil and water conservation measurement, namely bund terrace and silt pit that are combined with retarded-water hole on production of oil palm. Sampled trees of each block were randomly selected as much as 36 trees. Parameters of vegetative growth (additional new frond, total of frond, number of new bunch), production (number of bunch, fresh fruit bunch (TBS)), and average of bunch weigh (RBT) were observed and recorded every two weeks. Production of palm oil of each block was also recorded every harvesting schedule of Afdeling. Tabular data were analyzed descriptively by logical comparison among the blocks as result of application of bund terrace and silt pit. Although the data of sampled trees were erratic, bund terrace and silt pit generally increasing number of frond, number of bunch, average of bunch weight, and fresh fruit bunch. Bund terrace gived the highest production of TBS (25.2 t ha-1) compared to silt pit application (23.6 t ha-1), and it has better effect on TBS than block control (20.8 t ha-1). Aside from that, RBT is the highest (21 kg) at bund terrace block compared to silt pit block (20 kg) and control block (19 kg).